Analisis Peran Stakeholders Dalam Pengembangan Destinasi Pariwisata Halal Di Pulau Penyengat Provinsi Kepulauan Riau - Riska Destiana; Kismartini Kismartini; Tri Yuningsih (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
Pulau Penyengat is designated as a leading area for halal tourism development. The development of halal tourism on Pulau Penyengat requires cooperation and support from many parties. The less optimal role of stakeholders in tourism development cooperation makes the reason for the importance of this research being carried out. The purpose of this research is to identify the stakeholders involved, analyze the roles of stakeholders, analyze the relationships between stakeholders, and analyze supporting and inhibiting factors. The method uses a qualitative descriptive approach, with data collection techniques combining online interviews, documentation and observations. The results show that the development of the island's halal tourism destinations involves stakeholders with the pentahelix concept, consisting of academics, business, community, government and mass media. There are 38 stakeholders involved and classified into primary, key and secondary stakeholders. The role of stakeholders is reflected in the roles of policy creators, coordinators, facilitators, implementers and accelerators. The relationship between stakeholders is seen from the form and activities. Value and communication are supporting factors in the development of halal tourism destinations, and trust and policies are inhibiting factors. The suggestions conveyed are the issuance of halal tourism regulations, the formation of a special tourism agency for Pulau Penyengat ,increased coordination between stakeholders, increasing the role of academic and community stakeholders, improving halal tourism support facilities, and promoting halal tourism through digital channels.